CENTROID-MOMENT TENSOR SOLUTIONS FOR JANUARY-MARCH, 1983 - Dziewonski, A; Friedman, A; Woodhouse, J (1983)
Centroid-moment tensor solutions are presented for 89 earthquakes that occurred during the first quarter of 1983. © 1983.